2018
DOI: 10.1136/bmjopen-2017-019119
|View full text |Cite
|
Sign up to set email alerts
|

Patient confidence regarding secondary lifestyle modification and knowledge of ‘heart attack’ symptoms following percutaneous revascularisation in Japan: a cross-sectional study

Abstract: ObjectiveTo assess patient perspectives on secondary lifestyle modification and knowledge of ‘heart attack’ after percutaneous coronary intervention (PCI) for coronary artery disease (CAD).DesignObservational cross-sectional study.SettingA single university-based hospital centre in Japan.ParticipantsIn total, 236 consecutive patients with CAD who underwent PCI completed a questionnaire (age, 67.4±10.1 years; women, 14.8%; elective PCI, 75.4%). The survey questionnaire included questions related to confidence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Routine nursing service after PCI confines the focus of nursing to patients during hospitalization, implements clinical health education for patients about to be discharged, and informs patients of basic nursing services such as medication methods and dosage, which results in a “disruption” state after patients are discharged from hospital. For patients with low knowledge of their own diseases or more negative emotions, their medication compliance after discharge is worse [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Routine nursing service after PCI confines the focus of nursing to patients during hospitalization, implements clinical health education for patients about to be discharged, and informs patients of basic nursing services such as medication methods and dosage, which results in a “disruption” state after patients are discharged from hospital. For patients with low knowledge of their own diseases or more negative emotions, their medication compliance after discharge is worse [ 18 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the factors that influence patient knowledge is their past ACS experience or their coronary heart disease history. In addition, the patients who have a previous history will have the correct interpretation of symptoms [26] by taking a choice to come to the hospital immediately [27]. The gender factor also influences the interpretation of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The studies conducted in Japan suggested that patients have a high level of confidence about smoking cessation, alcohol restriction, and medication adherence. However, they had relatively low levels of confidence regarding the maintenance of blood pressure control, healthy diet, body weight, and regular exercise (≥3 times week) [27].…”
Section: Discussionmentioning
confidence: 99%
“…The investigator interviewed each respondent individually and at the end of their interview the participants were thanked for their participation. The investigator explained all the respondents in detail on lifestyle modifications and heart attack using a PowerPoint presentation, if they lacked any information [4][5][6].…”
Section: Methodsmentioning
confidence: 99%